ETHICAL POLITIC AND EMERGENCE OF INTELLECTUAL CLASS - Abdullah, Annzar (History Department, Semarang State University and Historian Society of Indonesia, 2017)
This study aimed to examine and analyze the relationship between the ethical and the birth of the educated classes in the Dutch East Indies (Indonesia) in the colonial period. The research is qualitative by using methods and approach to historical analysis. The methods and approach to historical analysis combined with interactive methods, interdisciplinary and inter-textual to gain an understanding of the diverse impulses and interactions that contributed to the birth of the educated classes in the Indian Dutch the colonial period. The results showed that the policy of